2022
DOI: 10.33487/edumaspul.v6i2.4370
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Transitivity System Used in Students’ Recount Texts at Islamic Boarding School

Abstract: The main objectives of this research are to explore the types of transitivity process used by tenth grade students in writing recount text at one of the Islamic Boarding Schools in Karawang and to describe the pedagogical implication of the use of transitivity analysis. This research employed qualitative approach to analyze the transitivity process of students' writing recount texts. The data in this research are five students’ recount texts. Five recount texts written by the students were purposively selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The bycatch composition of tuna longline is 24.08% byproducts and 49.74% discards. Bycatch is dominated by 42.87% Alepisaurus spp., 22.05% Pteroplatytrygon violacea, and 10.22% escolar/Lepidocybium flavobrunneum [3].…”
Section: Introductionmentioning
confidence: 99%
“…The bycatch composition of tuna longline is 24.08% byproducts and 49.74% discards. Bycatch is dominated by 42.87% Alepisaurus spp., 22.05% Pteroplatytrygon violacea, and 10.22% escolar/Lepidocybium flavobrunneum [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research regarding the implementation of transitivity in students' recount texts has been done before. Research done by (Elsie et al, 2020;Fajriah, 2021;Novianto et al, 2022;Rahayu & Efransyah, 2020;Rahmawati, 2019;Rosmayanti et al, 2021;Utami et al, 2022) revealed that the most prevalent material process found in the data for students' recount text was retelling something that happened in the past that the students experienced. This article will concentrate on the transitivity of students' writing recounts with quantitative and qualitative methods.…”
Section: Introductionmentioning
confidence: 99%